Pemanfaatan Daun Kelor untuk Inovasi Pembuatan Es Cendol di Desa Pendil Kecamatan Banyuanyar - Ryzca Siti Qomariyah; Afib Rulyansah; Arifatul Lutfiah; Tri Fatmawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2021)
The COVID-19 pandemic has made many people's economy decline, not a few people have their economy fulfilled. Business owners lost 50% of their customers. This causes the turnover of entrepreneurs to decrease. In order to attract customers, it is necessary to innovate the product. As in SMEs UD. ABC Cookies that use Moringa as the basic ingredient of cendol. This MSME development method is by innovating products from old Moringa leaves into Moringa powder, so that it becomes cendol, changing packaging to be more attractive, sticker and photo design, online marketing, customer service, and financial management. The output of this activity is that the 2021 UPM Thematic KKN students received new information about the benefits of old Moringa leaves which are usually not used by the public but can still be used as powder and become the basic ingredients of food and drinks. By utilizing old Moringa leaves, the surrounding community can contribute to depositing old Moringa leaves to be used as basic ingredients for food and drinks so that they are not wasted. This cooperation is mutually beneficial between the community and MSME owners.